Sosialisasi Optimalisasi Penginderaan Jauh Guna Meningkatkan Zona Potensi Penangkapan Ikan di Desa Sumare, Sulawesi Barat - Indah Yani, Fitri; Mutmainnah, Nurul; Rahmi; Jufri, Ady; Rusdi, Rismawaty (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The fisheries sector plays a vital role in the Indonesian economy, particularly for coastal communities. However, the abundant marine potential in Sumare Village, Simboro District, Mamuju Regency, has not been optimally utilized by local fishermen. Continuous traditional fishing in certain locations has led to environmental degradation and the potential for overfishing, which threatens the sustainability of the marine ecosystem. To address this problem, this community service activity aims to empower fishermen through the dissemination of remote sensing technology based on oceanographic parameters such as sea surface temperature (SST) and chlorophyll-a, to determine potential and sustainable fishing locations. The methods used included material delivery, discussions, and the distribution of banners displaying maps of potential skipjack tuna fishing zones. The results of this activity showed an increase in fishermen's understanding of remote sensing technology, potential fishing zones, and community enthusiasm in supporting this activity. In conclusion, this dissemination successfully provided important education for the Sumare village community to increase fishing efficiency, maintain the sustainability of fishery resources, and improve fishermen's welfare.